1993
DOI: 10.1126/science.8493533
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of V(D)J Recombination Activator Protein RAG-2 by Phosphorylation

Abstract: Antigen receptor genes are assembled by site-specific DNA rearrangement. The recombination activator genes RAG-1 and RAG-2 are essential for this process, termed V(D)J rearrangement. The activity and stability of the RAG-2 protein have now been shown to be regulated by phosphorylation. In fibroblasts RAG-2 was phosphorylated predominantly at two serine residues, one of which affected RAG-2 activity in vivo. The threonine at residue 490 was phosphorylated by p34cdc2 kinase in vitro; phosphorylation at this site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(124 citation statements)
references
References 44 publications
4
120
0
Order By: Relevance
“…As the non-core region of RAG2 is highly conserved throughout evolution, it was proposed that it regulates in vivo recombinase activity at one or more of the control layers mentioned above. One known function of this part of RAG2 is indeed to restrict DNA cleavage to the G0/G1 phase of the cell cycle and this is mediated by phosphorylation of T490 [ 16,17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the non-core region of RAG2 is highly conserved throughout evolution, it was proposed that it regulates in vivo recombinase activity at one or more of the control layers mentioned above. One known function of this part of RAG2 is indeed to restrict DNA cleavage to the G0/G1 phase of the cell cycle and this is mediated by phosphorylation of T490 [ 16,17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from Lin and Desiderio show that RAG-2 protein levels in transfected fibroblasts are regulated via a phosphorylation-dependent degradation pathway (Lin and Desiderio 1993). Furthermore, studies on the coordination of DNA repair with the cell cycle have revealed that cells sustaining DNA damage arrest their progression through the cell cycle until the damage has been repaired.…”
Section: Cell Cycle Regulation Of the V(d)j Recombinase Activitymentioning
confidence: 99%
“…5B). Furthermore, RAG2 protein, which can be regulated either at the mRNA level [25] or via phosphorylation and subsequent degradation in cycling cells [26,27], was not downregulated in DN (Fig. 5C) and DN3 (data not shown) thymocytes from all three strains of TCRb Tg mice.…”
Section: Pta-dependent Allelic and Isotypic Exclusion Occur Despite Nmentioning
confidence: 84%
“…The same result was obtained when sorted DN3 thymocytes were analyzed. [26] of the RAG proteins. With regard to the latter point, our failure to observe down-regulation of RAG1 mRNA or RAG2 protein expression in DN3 thymocytes in the presence of a TCRb transgene does not support a direct role for pre-TCR signaling in the regulation of RAG expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation